Science and Comparative Philosophy : Introducing Yuasa Yasuo - Shaner, David Edward; Nagatomo, Shigenori; Yasuo, Yuasa (Leiden, New York [etc.] : E.J. Brill, 1989)
Science and comparative philosophy / by David Edward Shaner -- The Japanese experience of nature / by David Edward Shaner -- The Japanese concept of self / by Shigenori Nagatomo -- Contemporary science and an Eastern mind-body theory / by Yuasa Yasuo -- A cultural background for traditional Japanese self-cultivation philosophy and a theoretical examination of this philosophy / by Yuasa Yasuo.
boek
Keywords: Yasuo, Yuasa